Biohemijski i klinički efekti kontinuiranog pozitivnog pritiska u disajnim putevima u kombinaciji sa sildenafilom na inflamatorne i hemodinamske profile kod gojaznih pacijenata sa astmom sa plućnom arterijskom hipertenzijom: Biochemical Impact of CPAP Plus Sildenafil in Obese Asthma with Pulmonary Hypertension - Bai, Wenmei; Wang, Nana; Wang, Zixuan; Wu, Zhimin; Luo, Xueying; Li, Fengsen (Journal of Medical Biochemistry, 2025)
Background: Obesity-associated asthma complicated by pulmonary arterial hypertension (PAH) involves multifactorial biochemical dysregulation, including endothelial dysfunction, oxidative stress, and chronic inflammation. This study aimed to evaluate the combined biochemical and clinical effects of continuous positive airway pressure (CPAP) and sildenafil on pulmonary function, inflammatory biomarkers, and hemodynamic parameters in obese asthma patients with PAH. Methods: A total of 134 patients (BMI ≥30 kg/m², FEV₁ < 70% predicted, PASP ≥ 30 mmHg) were enrolled and divided into a treatment group (n = 63, CPAP + sildenafil) and a comparison group (n = 71, sildenafil alone). Pulmonary and hemodynamic indices (PaO₂, FiO₂, PASP, OI, and PaO₂/FiO₂), lung function parameters (FEV₁, PEF), and asthma control test (ACT) scores were assessed at baseline and follow-up (6 and 12 months). Serum interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and fractional exhaled nitric oxide (FeNO) were quantified to evaluate biochemical inflammation. Correlation analysis was performed between biomarker changes and ACT improvements. Results: The CPAP + sildenafil group showed significantly higher post-treatment PaO₂ levels, lower PASP and FiO₂ values, improved OI, and greater increases in PaO₂/FiO₂ and FEV₁ percentages compared with the sildenafil-only group (P < 0.001). Biochemical assays revealed substantial reductions in serum IL-6 and TNF-α levels, as well as FeNO concentrations, in the combination group. Post-treatment changes in IL-6 (r = 0.68, P < 0.0001), TNF-α (r = 0.59, P < 0.0001), and FeNO (r = 0.72, P < 0.0001) were strongly correlated with improved ACT scores, suggesting a close biochemical–clinical relationship between airway inflammation and therapeutic response. Conclusion: CPAP combined with sildenafil exerts dual biochemical and clinical benefits in obese asthma patients with PAH by enhancing oxygenation, lowering pulmonary artery pressure, and suppressing inflammatory cytokine activity. The observed reductions in IL-6, TNF-α, and FeNO highlight the biochemical basis of treatment efficacy and the potential of these markers as laboratory indicators for monitoring therapeutic outcomes.